MEDIA PEMBELAJARAN IPA LECTORA INSPIRE BERBASIS INKUIRI DAUR HIDUP HEWAN KELAS IV SDN 44 KALUMBUK PADANG - Akma Arif; Enjoni Enjoni; Febri Yanto (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
The results of an interview with one of the teachers at SD 44 Kalumbuk told that teaching various science materials during the Normal period used picture media, while during the Covid-19 Pandemic the teacher used the WA application, making it difficult for the teacher to explain the material directly to students. A learning media application is needed to deliver science material. This research aims to produce learning media through the Lectora Inspire application that is valid and practical based on inquiry in Science Theme 6 class IV My Dreams at SD Negeri 44 Kalumbuk. This type of research is research and development (Research and Development). The research model used is the 4-D type, namely define, design, develop, and disseminate. In this study, it only reached the development stage due to time constraints and the spread of the Corona Covid-19 virus. This research was conducted in the even semesters of the 2020/2021 school year. Based on the results of the Material Validation Test, Design and Language. Lectora Inspire media is very valid to use. Overall, the results of the Validation Test with a percentage of 91.36% are at the number 3.53 with the very valid and feasible category. The media design validation test was at a percentage of 85.7%, the material validation was 97.5%, while the language validation test was at a percentage of 90.9%. Can be used in class IV Animal Life Cycle Material Theme 6 My Dreams. Whereas in the Practicality Test of student responses, with the subject of fourth grade students of SDN 44 Kalumbuk, Padang city, totaling 30 students, were at a percentage of 94.58% and the teacher's response with 2 observers was 97.33% in the category of very practical. Overall, Inquiry-based Lectora Inspire learning media is very valid and very practical to use in grade IV SDN 44 Kalumbuk with the theme 6 My Dreams Subtema 2 Amazingly My Dreams.